2019
DOI: 10.5424/fs/2019283-15233
|View full text |Cite
|
Sign up to set email alerts
|

The use of physiological, biochemical and morpho-anatomical traits in tree breeding for improved water-use efficiency of Quercus robur L.

Abstract: Aim of study: In the present paper we studied the nature and level of co-dependence between leaf functional traits and intrinsic water-use efficiency (WUEi)in one-year-old Quercus roburL. seedlings, grown in a common garden experiment under moderate drought conditions. The study aimed to identify those traits that might be potentially utilized to improve leaf-level WUEi, and therefore be used in breeding programmes to enhance drought adaptation of Q. roburtree species.Area of study: The study was carried out a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…In addition, there was a significant negative correlation between WUE on one side, and SD, gs and A, on another, suggesting that plants with lower stomatal density tend to have higher water-use efficiencies, as well as reduced CO 2 uptake, and consequently, lower assimilation rates (Drake et al 2013). Our results are also in agreement with the findings of Stojnić et al (2019) who demonstrated that variation of WUE in Q. robur half-sib lines was strongly dependent on both SD and FRAP.…”
Section: Relationship Between Leaf Functional Traitssupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, there was a significant negative correlation between WUE on one side, and SD, gs and A, on another, suggesting that plants with lower stomatal density tend to have higher water-use efficiencies, as well as reduced CO 2 uptake, and consequently, lower assimilation rates (Drake et al 2013). Our results are also in agreement with the findings of Stojnić et al (2019) who demonstrated that variation of WUE in Q. robur half-sib lines was strongly dependent on both SD and FRAP.…”
Section: Relationship Between Leaf Functional Traitssupporting
confidence: 91%
“…Based on Pearson's correlation analysis, a significant positive correlation was found between gs and SL (r = 0.53), confirming the results of Dow et al (2014) who found evidence that stomatal conductance is affected by stomatal aperture characteristics. Similar results were also reported by Stojnić et al (2019) for Q. robur half-sib progenies. Likewise, PCA showed a positive relationship between gs and SD, which corresponds to the results for different plant species (Pearce et al 2006;Xu and Zhou 2008).…”
Section: Relationship Between Leaf Functional Traitssupporting
confidence: 90%
See 2 more Smart Citations
“…Species characterized with higher WUEi values have specific water-saving strategy to avoid greater water losses and maintain higher assimilation rates, particularly important under the conditions of predicted climate changes (Brendel et al 2008). Taking into account the effectiveness of WUEi as an indicator of drought sensitivity, the importance of identification of traits that could be utilized to improve WUEi and hence enhance drought adaptation in breeding programmes was noted (Stojnić et al 2019). M. grandiflora exhibited a higher ability to tolerate the prolonged period of drought compared to M. soulangeana, by maintaining greater values of A and WUEi.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%